Strategic Options for the Expansion of South African Retail Businesses within Africa: Consequences on Operational Management - Dakora, Edward A.N.; . André Slabbert (Journal of Economics and Behavioral Studies, 2014)
The expansion of retail companies across national borders is a global phenomenon that is becoming a reality in Africa. This phenomenon is led largely by South African retailers as they seek new markets in Africa. The continent presents both market opportunities as well as challenges. Yet there has been limited academic research on the management of the complexities faced by these retail companies. This paper examines the strategic options available to senior retail management regarding entry mode choices and the possible factors that influence management decisions as they expand their business activities into Africa. The paper also attempts to echo the consequences of such strategic decisions on operational management when it comes to managing operations abroad. It does so by employing mixed method approaches which include analysis of in-depth interviews with senior managers of five major South African retailers, and results of an online survey of retail workers in Cape Town, using the Principal Component (factor) Analysis technique in SPSS. This resulted in six broad factors which appear to provide unique insight on issues that affect the entry mode choices of South African retailers seeking new markets in Africa. The paper concludes that retail managements making this move are often caught up between management self-confidence and their ability to manage risk.